Quality of life and eating attitudes of health care students - Daniela Galdino Costa; Cíntia Tavares Carleto; Virgínia Souza Santos; Vanderlei José Haas; Rejane Maria Dias de Abreu Gonçalves; Leila Aparecida Kauchakje Pedrosa
ABSTRACT Objective: To assess the quality of life and eating attitudes of health care students of the undergraduate programs of a public university. Method: Observational, cross-sectional, and quantitative study performed in a federal university. Three questionnaires were used for data collection: a socio-demographic and academic, the WHOQOL-BREF and the Eating Attitudes Test (EAT-26). Result: 399 students participated in this study, most women, average age of 22 years, average scores of EAT-26 of 15.12 and quality-of-life averages above 60 points in all domains. The students of the undergraduate program in Nutrition presented more inappropriate eating attitudes than other health care students; as the age evolves, vulnerability to inadequate eating attitudes increases; and the family income influenced negatively the quality of life in Physical and Social domains. Conclusions: Inadequate eating attitude diminishes the quality of life of health care students in all domains of the WHOOQOL-BREF.